2021
DOI: 10.1111/sms.13929
|View full text |Cite
|
Sign up to set email alerts
|

Distal‐to‐proximal joint mechanics redistribution is a main contributor to reduced walking economy in older adults

Abstract: Age‐related neural and musculoskeletal declines affect mobility and the quality of life of older adults. To date, the mechanisms underlying reduced walking economy in older adults still remain elusive. In this study, we wanted to investigate which biomechanical factors were associated with the higher energy cost of walking in older compared with young adults. Fourteen younger (24 ± 2 years) and fourteen older (74 ± 4 years) adults were tested. Plantarflexor strength and Achilles tendon stiffness were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 58 publications
(180 reference statements)
1
14
0
Order By: Relevance
“…This reduction when walking shows a change in walking strategy made by older people who tend to transmit forces through the hip joint by developing greater torques. These findings have been described as a limiting factor for elderly adults as they are obliged to adjust their walking pattern as the gait speed increases [ 11 , 12 , 13 ] or when climbing stairs [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction when walking shows a change in walking strategy made by older people who tend to transmit forces through the hip joint by developing greater torques. These findings have been described as a limiting factor for elderly adults as they are obliged to adjust their walking pattern as the gait speed increases [ 11 , 12 , 13 ] or when climbing stairs [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main changes in walking mechanics are manifested by a decrease in the ankle and hip joint torques [ 1 , 10 , 11 ]. This reduced ability to generate joint torques has been described as a limiting factor in walking speed and a modifier of walking patterns [ 12 , 13 ]. In addition, reduced motor ability has been described as a factor in musculoskeletal disorders and injuries [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was theorized that with age, the stiffness of tendons might decrease due to mucoid degeneration and the loss of organized collagen fibrils [26]. However, a series of clinical research results found no significant correlation between the stiffness of the Achilles tendon and other tendons and age in healthy people of different ages [27, 28]. At the same time, we also included age in the subsequent multiple linear regression analysis, finding that age was not a significant influencing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological satisfaction of older adults is also widely regarded as a predictor of social inclusion because psychological satisfaction can be enhanced by increasing the mobility and independence of vulnerable groups within the built environment ( Chen et al, 2019 ; Zhang et al, 2022 ). Thus, many studies have explored the wellbeing of older adults in the development process of cities and regions from the perspectives of community support and health services ( Sexton and Bedford, 2016 ), family pressure ( Santis, 2012 ), voluntary or paid work ( Sagherian et al, 2021 ), and consumption and economy ( Delabastita et al, 2021 ). Studies have all acknowledged that progress in the built environment correlates with improved psychological wellbeing for older adults.…”
Section: Introductionmentioning
confidence: 99%